PARTISIPASI MASYARAKAT YANG BERMAKNA DALAM PEMBENTUKAN UNDANG-UNDANG PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 - Arman Surya Nicolas Marbun (2023)
This research is intended to examine the process and position of community participation in the formation of the law. This research is motivated by the Constitutional Court Decision No. 91/PUU-XVIII/2020 concerning the Job Creation Act, that in the Formation of Laws it is necessary to implement meaningful Public Participation. This research uses normative juridical and empirical juridical approach methods. The results of the study indicate that community participation has undergone significant changes in accommodating the aspirations of the people who are increasingly active in participating in shaping the law. In accordance with the second amendment to Law 12/2011 on the Formation of Laws and Regulations, it accommodates the results of public participation to be brought back and considered in the Law Formation process. However, any public participation needs to be done properly and not just as a formality.